Characterisation and numerical modelling of the geometry of rock joints - Resende, R.; Ramos, A.; Muralha, J.; Fortunato, E.; Lamas, L. (ISRM International Symposium: 8th Asian Rock Mechanics Symposium, Proceedings, 2014)
This paper describes the measurement and analysis of the roughness of natural rock joints with the aim of proceeding to their characterisation and comparison. Eight rock joints (corresponding to sixteen surfaces) were scanned with a three-dimensional scanner. This was followed by the description and characterisation of the surface roughness, as well as its reproduction and generation using techniques such as fractal models and Fourier transforms. Shear tests under constant normal load were performed, the joint surfaces were again scanned, and the resulting roughness surfaces were compared allowing the evaluation of asperity breakage and surface wear. One of the joint specimens was tested under several normal stresses, which allowed the estimation of its mechanical characteristics, and was scanned after each test to evaluate the influence of the normal and shear load on the variation of roughness. The scans of the rock joints produced accurate numerical descriptions of their topologies, allowing countless possibilities of future studies, such as the study of the matching of rock joints by the numerical adjustment of bottom and top surfaces, the statistical and geostatistical characterisation of rock joints or the degradation of roughness after normal and shear tests. This paper presents an overview of the research work that is still under way.